Readability Analysis of Ecology Laboratory Manual: Evaluation and Recommendations - Zulhendri, Zulhendri (Biocaster : Jurnal Kajian Biologi, 2024)
This study aims to describe or analyze the readability of ecology laboratory manuals, evaluate their effectiveness, and provide recommendations for improvement. This research is descriptive. The data collection technique employed readability tests, while data analysis utilized percentage techniques. The research findings indicate an average readability test score of 74.66%, categorized as valid. These results suggest that the laboratory manual is valid and does not require revision, making it suitable for use by students.